2016
DOI: 10.1021/acsbiomaterials.6b00233
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) Hydrogels with Tailorable Surface and Mechanical Properties for Tissue Engineering Applications

Abstract: Advanced cellular biomanufacturing requires the large-scale production of biocompatible materials that can be utilized in the study of cell-matrix interactions and directed stem cell differentiation as well as the generation of physiologically relevant tissues for therapeutic applications. Herein we describe the development of a hydrogel based platform with tailorable mechanical properties that supports the attachment and proliferation of both pluripotent and multipotent stem cells. The biomimetic hydrogel sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Previously, we demonstrated the generation of biomaterial scaffolds of varying elasticity by implementing tailorable PEG hydrogels. Results showed that our hydrogel platform is compatible with multiple stem cell types, specifically mouse embryonic stem cells, human adipose stem cells and human bone marrow-derived MSCs (hMSCs) [ 17 ]. Here, we further characterize the interactions of our hydrogel platform with hMSCs, presenting an investigation into the specific interactions between hMSCs and our tailorable, affordable and reproducible PEG-based hydrogel platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated the generation of biomaterial scaffolds of varying elasticity by implementing tailorable PEG hydrogels. Results showed that our hydrogel platform is compatible with multiple stem cell types, specifically mouse embryonic stem cells, human adipose stem cells and human bone marrow-derived MSCs (hMSCs) [ 17 ]. Here, we further characterize the interactions of our hydrogel platform with hMSCs, presenting an investigation into the specific interactions between hMSCs and our tailorable, affordable and reproducible PEG-based hydrogel platform.…”
Section: Introductionmentioning
confidence: 99%
“…For conciseness, the hydrogels with an elastic modulus of 50–60 kPa are referred to as ‘stiff hydrogels’ and the hydrogels with an elastic modulus of 8–10 kPa are referred to as ‘soft hydrogels’. Expanding on our previous work, here we demonstrate the utilization of our PEG-based hydrogel blends to study the effect of elasticity on the characteristics and differentiation potential of bone marrow-derived MSCs [ 17 ]. We show that the hydrogels of different elasticities produce changes in hMSC morphology and proliferation, which provides support that the platform has the potential to produce changes in hMSC behavior and cell state.…”
Section: Introductionmentioning
confidence: 99%
“…The library exhibits a wide range of compressive moduli from 3.57 KPa to 6.4 MPa, which could mimic a wide range of tissues from soft tissue such as brain and adipose tissue to stiffer cancellous bone. 18,22,23 As shown in Figures 6 and 7, the compressive moduli (E) of the hydrogels increased with PEG-DA concentration. Through a combination of prolation and subsequent molecular relaxation by removal of the porogen, decreasing material stiffness was achieved.…”
Section: Physicochemical Characterization Of Crosslinked Hydrogelmentioning
confidence: 76%
“…Biocompatible fibers are useful for spot illumination, but cannot be employed by themselves to target larger tissue areas. Light guiding hydrogels offer great versatility in their optical and mechanical properties [8][9][10] , can be engrafted into the target tissue 11 and are already in use for tissue engineering purposes 12 . Hydrogel waveguides are already being tested in live tissues for applications such as sensing or phototherapies 9,13 .…”
Section: Hydrogels As Implantable Waveguidesmentioning
confidence: 99%